Neutrophil to Lymphocyte and Platelet to Lymphocyte Ratios in Peritoneal Dialysis-Related Peritonitis - Gurel, Ali; Dogukan, Ayhan; Celiker, Huseyin; Ulu, Ramazan; Yigit, Irem Pembegul; Aygen, Bilge (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2015)
OBJECTIVE: Peritonitis is an important problem for peritoneal dialysis (PD) patients. It has been demonstrated that the erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) increase nonspecifically in end-stage renal disease (ESRD) without infection. The neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) have been recently investigated as a new alternative inflammatory parameter to distinguish infections and other inflammatory events in a number of studies. We aimed to investigate the diagnostic value of NLR and PLR in bacterial PD peritonitis. MATERIAL and METHODS: In this study, we evaluated 40 peritonitis episodes that we treated. NLR and PLR were calculated from the same blood sample at the beginning and after the treatment of peritonitis. The same parameters were evaluated for 20 control subjects. RESULTS: Classical inflammatory markers such as CRP and ESR; NLR and PLR decreased with the successful treatment of peritonitis, and levels of these parameters were significantly different between the periods (p<0.05). CONCLUSION: Both NLR and PLR are valuable markers to follow the course of peritonitis and response to the treatment of peritonitis in correlation with conventional inflammation markers of infection. NLR and PLR are also more simple to calculate and cheaper parameters than classical markers.
Keywords: Peritoneal dialysis; Peritonitis; Neutrophil to lymphocyte ratio; Platelet to lymphocyte ratio